Asuhan Keperawatan Jiwa Pada Ny. M Dengan Gangguan Sensori Persepsi: Halusinasi Pendengaran Akibat Skizofrenia Schizoaffective Disorder Di Ruang Madrim RSJD dr. Amino Gondohutomo Provinsi Jawa Tengah - Rani Sopiya Sari; Titi Sri Suyanti; Slamet Wijaya B (Universitas Katolik Widya Karya Malang, 2023)
Covid-19 has become a disease outbreak with an alarming level of spread and severity. The Covid-19 pandemic not only affects physical health, but also affects a person's mental health (Advocacy, 2020). The spread of Covid-19 throughout the world has caused the global health status to become a pandemic. Apart from causing physical problems for humans, the Covid-19 pandemic can also cause stress and increase the risk of various mental problems (Pfefferbaum & North, 2020). Apart from that, 53.8% of people felt psychological impacts such as depression, anxiety and stress due to Covid-19 (Wang et al., 2020).